A comparative analysis of theoretical concepts in international trade law unification definition (International relations and international law Journal, 2016)
The article, based on a comprehensive study of doctrinal approaches to basic concepts and legal contents institute for the unification of international trade law, were installed objective preconditions and factors that contribute to the implementation of this process, defined by its integrated (cross-sectoral) affiliation. A study of the unification of international trade law was considered in the framework of national (civil) law and private international law. However, attention was drawn to the public aspects of legal unification, because the word «unification» means, first of all, the process of active action on the part of power, public bodies. Analyzed the correlation of the concepts of harmonization, convergence and unification, the author is given a broader, expanded definition of «unification of international trade law» with regard to the state of development of modern economic relations of states.
Keywords: unification of international trade law; harmonization; convergence; uniform standard